Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1002/cssc.202100433
|View full text |Cite
|
Sign up to set email alerts
|

Green Hydrothermal Synthesis of Fluorescent 2,3‐Diarylquinoxalines and Large‐Scale Computational Comparison to Existing Alternatives

Abstract: Here, the hydrothermal synthesis (HTS) of 2,3‐diarylquinoxalines from 1,2‐diketones and o‐phenylendiamines (o‐PDAs) was achieved. The synthesis is simple, fast, and generates high yields, without requiring any organic solvents, strong acids or toxic catalysts. Reaction times down to <10 min without decrease in yield could be achieved through adding acetic acid as promoter, even for highly apolar biquinoxalines (yield >90 % in all cases). Moreover, it was shown that HTS has high compatibility: (i) hydrochloride… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 50 publications
(62 reference statements)
1
16
0
Order By: Relevance
“…In a first experiment, we reacted equimolar amounts of 4,4′-dimethoxybenzil ( 1 ) and 3,4-diaminobenzoic acid ( 2 ) in 5% HOAc under the previously reported conditions, i.e., T r = 230 °C, t r = 10 minutes. 12 As expected, analysis of the crude product by 1 H NMR showed that the target quinoxaline 3 was obtained as the major product. However, further signals suggested the presence of a second product in a lower amount than compound 3 .…”
supporting
confidence: 69%
See 2 more Smart Citations
“…In a first experiment, we reacted equimolar amounts of 4,4′-dimethoxybenzil ( 1 ) and 3,4-diaminobenzoic acid ( 2 ) in 5% HOAc under the previously reported conditions, i.e., T r = 230 °C, t r = 10 minutes. 12 As expected, analysis of the crude product by 1 H NMR showed that the target quinoxaline 3 was obtained as the major product. However, further signals suggested the presence of a second product in a lower amount than compound 3 .…”
supporting
confidence: 69%
“…The HTS of quinoxalines is compatible with a broad scope of starting materials bearing diverse functional groups. However, in our recent work, 12 we did not investigate substrates bearing carboxylic acids (CO 2 H) as ( i ) they might condense with the amino groups available in o -PDA analogues towards forming, e.g., benzimidazoles, or ( ii ) decarboxylation of the CO 2 H functions might occur in HTW. In the present work, we address the compatibility of the HTS of quinoxalines with carboxylic acid groups.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Aside PIs, HTP has recently been shown to be also amenable to the synthesis of polyamide networks, which in the reported example are, however, linked by linear amide functions (and hence no heterocyclic linkages), and based on both aromatic and also alicyclic moieties, 22 polyazomethines (also not featuring heterocyclic linkages but linear azomethine (aka secondary aldimine) linkages), 23 and polybenzimidazoles and benzoyl-imidazole polymers (aka BBB – benzimidazolebenzophenanthroline-type semiladder polymers). 24 HT cyclocondensations can also be used for generating small organic molecules, the technique is then rather termed hydrothermal synthesis (HTS), with examples comprising rylene bisimides, 25 benzimidazoles, 26 quinoxalines, 76 and the fused bisbenzoylimidazole perinone. 27 HTS/HTP relies on superheated liquid H 2 O as medium, generated through heating H 2 O above its boiling point in a closed vessel (typically an autoclave).…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by this geothermal process, hydrothermal reaction occurring under high temperature and pressure can offer a convenient access toward the synthesis of a range of crystalline materials, such as gemstones, zeolites, and carbonaceous materials [4] . In addition, the use of hydrothermal reactions is promising for the synthesis of organic materials because of its simplicity, environmental sustainability, and low cost [5–9] …”
Section: Introductionmentioning
confidence: 99%